Validation of 6 min step test and 4-m gait speed in children: A randomized cross-over study - Reychler, G.; Audag, N.; Dewulf, S.; Morale Mestre, N.; Caty, G. (Gait and Posture, 2018)
Even if 6-min walking test (6MWT) is the criterion standard for functional exercise performance evaluation, new field tests are required as practical alternative. This study aims to establish the validity of the 6-min step test (6MST) and the 4-m gait speed (4MGS) in children. Method: It is a randomized cross-over trial. Sixty one healthy children from 6 to 12 years were recruited. 6MWT, 6MST and 4MGS were randomly performed on three consecutive days. Pulsed oxygen saturation (SpO2), heart rate (HR), dyspnea (VAS) and fatigue (PCERT) were used as outcomes. Results: The distance walked during 6MWT was correlated to the number of steps during 6MST (r=0.320; p=0.013) and not correlated to 4MGS (r=-0.074; p=0.575). No correlation between number of steps during 6MST and 4MGS (r=-0.129; p=0.332) was found. HR was lower than the theoretical maximal HR after the tests. The increase in HR was significantly higher for 6MST and significantly lower for 4MGS than for 6MWT and it was higher for 6MST than for 4MGS. Dyspnea and perceived exertion were lower after 6MWT than after 6MST and higher than after 4MGS. They were also higher during 6MST than during 4MGS. Conclusion: The three field tests are feasible in children. The 6MST and 4MGS are not valid surrogates to 6MWT in healthy children for functional exercise performance evaluation. Moreover, the cardio-respiratory response differs between the three tests